Voice Enabled Smart Home Assistant for Elderly - Perumal, Sujitha; Javid, Mohammed Saqib (International Journal of Computer Sciences and Engineering, 2019)
In this paper we present our project that focuses on developing a Voice enabled Smart Home Assistant that will help find items in a home and also support natural and secure interaction using voice recognition.The software will be helpful for elderly people and those with Alzheimer`s disease to help find items at home. It can also be used by people who often forget where they keep their things as well as large organizations to manage complex inventory, without the friction and multiple steps of keeping inventory updated. The project will be relevant to society, as users will be able to communicate with the Smart Home Assistant in a natural way and security will also be ensured as no unknown users will have access to the software. The software can also be accessed through mobile application.The Voice enabled Smart Home Assistant will employ natural language processing techniques to understand the user’s request to identify the location of the object and report it to the user. The software will be integrated with Amazon Alexa which is a cloud-based voice service and the users can access the software using the Amazon Echo device.